Fiscal policy in the Federal Republic of Germany - Wolfgang Franz (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1989)
The main purpose of this paper is at least twofold. Firstly, the paper gives a record of fiscal policy in the Federal Republic of Germany by describing various phases of its design during the past twenty years. This is done on the background of changing economic conditions and different monetary regimes. As a second purpose, the paper attempts to evaluate the performance of fiscal policy in the Federal Republic of Germany both by taking stock of some empirical results obtained in other studies and by own econometric investigations. The goal of the econometric analysis is to estimate fiscal and monetary policy rules by taking into account explicitly the possibility that these policies have to be treated as at least partly endogenous variables. As a major outcome of the first purpose, three phases of fiscal policy may be distinguished. While the first phase is characterized by a short-term oriented global demand management prevailing until the mid-seventies, fiscal policy was more in favor of a steadily oriented growth and structural policy afterwards. This phase was succeeded by an embarkment upon a cause of fiscal consolidation since the beginnings of the eighties. With respect to the effectiveness of fiscal policy actions, our own econometric analysis is based on a four equations model. Basically it consists of a conventional IS-LM model with a very simple Phillips curve. In addition, fiscal and monetary reaction functions are estimated in order to avoid biased coefficients associated with the impact of fiscal and monetary impulses on employment. It is shown, how important it is (econometrically) to treat policies as endogenous variables. Moreover, our results point to the well-known experience that only a combination of expansive fiscal and monetary measures is suitable to fight against unemployment.
Keywords: 330